Suitable coverage and slope guided by soil and water conservation can prevent non-point source pollution diffusion: A case study of grassland - Guirong Hou; Jiangkun Zheng; Xinglei Cui; Fang He; Yunqi Zhang; Yong Wang; Xianwei Li; Chuan Fan; Bo Tan (Ecotoxicology and Environmental Safety, 2022)
Non-point source pollution caused by surface runoff has been a popular hydrological and environmental safety issue and has attracted extensive attention from global scholars. To identify the optimal vegetation coverage of Festuca arundinacea grassland for controlling soil erosion and purifying surface runoff, bare land was chosen as the control in this experiment. Simulated rainfall experiments were carried out with three levels of coverage (low coverage, moderate coverage and full coverage) under four slope conditions (flat slope, gentle slope, medium slope, and steep slope) and at four rainfall intensities (moderate rainfall, heavy rainfall, rainstorm and heavy rainstorm). The comprehensive evaluation results suggested that the capacity of Festuca arundinacea grassland for reducing the surface runoff, sediment yield, suspended solids (SS), total nitrogen (TN), total phosphorus (TP) and chemical oxygen demand (COD) decreased with increasing rainfall intensity and slope but increased with increasing vegetation coverage. Structural equation model (SEM) results suggested that there were positive relationships between the vegetation coverage and purification capacity index and negative correlations between the rainfall intensity and slope and the purification capacity index. The response surface analysis results suggested that the optimal vegetation coverage should be higher than 84% and that the slope should be smaller than 10° for controlling soil erosion and avoiding pollution via diffusion with surface runoff in Festuca arundinacea grassland. This study proposes recommendations for the vegetation configuration pattern in the development and management of runoff purification systems.